Traditional and innovative values in the dynamics of changes caused by the conditions of globalization (Journal of Philosophy Culture and Political Science, 2023)
The continuous change in the value orientations of members of society sets the task of studying this process. Therefore, we consider it relevant in modern research to determine the relationship between traditional and innovative values in the dynamics of changes caused by the conditions of globalization. The main purpose of this article is to systematize the conclusions related to the proposed problem from the point of view of philosophical, political, and cultural studies. To achieve the goal, we set the task of substantiating the essence of the concept of traditional values by determining the essence of the concepts of «tradition» and «innovation» in the understanding of innovative values. To do this, first of all, in the introduction, we defined the basic formulations of the concept of globalization. In the first part of the results and discussion of the research work, a description of a number of basic approaches to traditional values was presented. As a result of the characteristics of these approaches, 4 main values and 4 characteristic features of traditional values are determined. The second part of the article focuses on the meaning of the concepts of «tradition» and «innovation». The influence, properties, and functions of traditional and innovative values on the lives of members of society are systematized. We came to the conclusion that in a society where political modernization and continuous political reforms take place, a social space is being formed where traditional and innovative values coexist.Key words: globalization, traditional values, innovative values, political and social institutions, post-industrial society, technologies